Experimental and numerical investigation on the long-term performance of engineered cementitious composites (ECC) with high-volume fly ash and domestic polyvinyl alcohol (PVA) fibers. (1st July 2023) - Lu, Cong; Pang, Zhiming; Chu, Han; Leung, Christopher K.Y.
Abstract: High-volume fly ash (FA) has been widely adopted to improve the mechanical properties and material greenness of engineered cementitious composites (ECC). However, the secondary hydration of fly ash leads to delayed strength gain over the long term, which may cause the composites to invalidate the long-term strain hardening performance. In this study, multiple-scale experiments conducted on ECC with high-volume FA (FA/cement = 4 by weight) and domestic polyvinyl alcohol (PVA) fibers at curing ages of 28, 90, 180, and 365 days showed that the fiber/matrix interfacial bonding, matrix compressive strength, and fracture toughness gradually increased with curing time and plateaued at a certain value after 180 days, while the tensile strain capacity continued to decrease with age. Based on the micromechanical parameters tested at different ages, a physical model was developed to simulate and reasonably predict the tensile performance of ECC with time. Design guidelines were proposed based on the model to enhance the robustness of the ECC's long-term performance. Highlights: The long-term performance of ECC with high-volume fly ash and domestic PVA fibers was studied by muti-scale experiments. A physical model based on the evolution of micromechanical parameters was proposed to predict the tensile property of ECC. Design guidelines for enhancing the long-term performance of ECC were proposed based on the proposed model.